Novel High-Throughput Detection Method To Assess Bacterial Surfactant Production - Adrien Y. Burch; Briana K. Shimada; Patrick Browne; Steven E. Lindow (2010)
A novel biosurfactant detection assay was developed for the observation of surfactants on agar plates. By using an airbrush to apply a fine mist of oil droplets, surfactants can be observed instantaneously as halos around biosurfactant-producing colonies. This atomized oil assay can detect a wide range of different synthetic and bacterially produced surfactants. This method could detect much lower concentrations of many surfactants than a commonly used water drop collapse method. It is semiquantitative and therefore has broad applicability for uses such as high-throughput mutagenesis screens of biosurfactant-producing bacterial strains. The atomized oil assay was used to screen for mutants of the plant pathogen Pseudomonas syringae pv. syringae B728a that were altered in the production of biosurfactants. Transposon mutants displaying significantly altered surfactant halos were identified and further analyzed. All mutants identified displayed altered swarming motility, as would be expected of surfactant mutants. Additionally, measurements of the transcription of the syringafactin biosynthetic cluster in the mutants, the principal biosurfactant known to be produced by B728a, revealed novel regulators of this pathway.